Improving dental health of fisherman’s families in the shipyard, Tallo-Makassar: Peningkatan kesehatan gigi keluarga nelayan di galangan kapal Tallo, Makassar - M. Ruslin; A. Tajrin; Surijana Mappangara; Hendrastuti Handayani; Andi Mardiana Adam; Sri Oktawati (Makassar Dental Journal PDGI Makassar, 2020)
This community service activity is carried out to increase understanding of dental and oral health in the community, carried out in the Fisheries Kampung Galangan Kapal Region, Tallo District, Makassar. The problem in this area is the lack of understanding of oral health so that people are less concerned about oral hygiene, the lack of public knowledge about the availability of dental and oral health service facilities has an impact on the lack of community visits. The solution taken is to provide education about oral health in daily life, using poster media, demonstrations and the distribution of pocket books. The expected output target is to increase dental health knowledge which will be followed by an increase in dental and oral health knowledge in the community. The method used is to provide counseling, direct demonstration, examination and prevention of dental and oral diseases. Activities undertaken are counseling to the mother, examination and care for the mother, as well as preventive measures on the child and ending with a final evaluation.